Conformational modulation and hydrodynamic radii of CP12 protein and its complexes probed by fluorescence correlation spectroscopy. (1st July 2014) - Moparthi, Satish Babu; Thieulin‐Pardo, Gabriel; Mansuelle, Pascal; Rigneault, Hervé; Gontero, Brigitte; Wenger, Jérôme
<x xml:space="preserve">Abstract</x> Light/dark regulation of the Calvin cycle in oxygenic photosynthetic organisms involves the formation and dissociation of supramolecular complexes between CP12, a nuclear‐encoded chloroplast protein, and the two enzymes glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) (EC 1.2.1.13) and phosphoribulokinase (PRK) (EC 2.7.1.19). Despite the high importance of understanding the structural basis of the interaction of CP12 with GAPDH and PRK to investigate the regulation of the Calvin cycle, information is still lacking about the structural remodulation of CP12 and its complex formation. Here, we characterize the diffusion dynamics and hydrodynamic radii of CP12 from Chlamydomonas reinhardtii upon binding to GAPDH and PRK using fluorescence correlation spectroscopy experiments. We quantify a hydrodynamic radius of 3.4 ± 0.2 nm for the CP12 protein with an increase up to 5.2 ± 0.3 nm upon complex formation with GAPDH and PRK. In addition, unfolding experiments reveal a 1.6‐ and 2.0‐fold increase respectively of the hydrodynamic radii for the N‐terminal and C‐terminal cysteine CP12 mutant proteins compared with their native folded structures. The different behavior of the CP12 mutant proteins during hydrophobic collapse transition is a direct clue to different structural orientations of the CP12 mutant proteins. These different structures are expected to facilitate the binding of either GAPDH or PRK during binary complex and ternary complex formation. Structured digital abstract GAPDH, CP12 and PRK physically interact by fluorescence correlation spectroscopy (View interaction) CP12 and PRK bind by fluorescence correlation spectroscopy (View interaction) GAPDH and CP12 bind by fluorescence correlation spectroscopy(View interaction)